Mortality from the 1944–1945 famine in Java, Indonesia - Eng, Pierre (Asia-Pacific economic history review, 2024)
This article examines the human toll of the 1944–1945 famine in Java, Indonesia's main island. It estimates birth and death rates for the Indonesian population in Java during 1941–1951. Using the net population loss method, the article approximates a net loss of 3.3 million people during the 1942–1945 Japanese occupation period. This includes 1.8 million excess deaths; 0.7 million during 1944 and 1.1 million during 1945. The remainder are 1.4 million missing births in 1944 and 1945, associated with the malnutrition of women of childbearing ages and physical separation of wives from husbands recruited by Japanese authorities for forced labour.